The Influence of Short Animation Movies Learning Listening Skills of 11th Graders at Ma Mu'min Cendekia Bekasi - Maulana, Siti Masitoh; Siahaan, Leroy Holman; Subadar, Subadar (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine whether there is a significant influence of the use of short animation movies on ‘learning of listening skills of class 11 Ma Mu'min Cendekia Bekasi.This study uses a Non-Experimental Quantitative method. There is no research sample because it is already in the surrounding environment. The researcher uses statistics, data analysis using SPSS 27. The researcher found learning problems in schools, namely that students' hearing is not clear, and they cannot hear the word